2021
DOI: 10.3390/diagnostics12010020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Depth of Invasion and Tumor Thickness as a Prognostic Factor for Early-Stage Oral Squamous Cell Carcinoma: A Retrospective Study

Abstract: The aim of this study was to compare the effect of using depth of invasion (DOI) versus tumor thickness (TT) as a prognostic factor for early-stage oral squamous cell carcinoma (OSCC). A total of 57 patients with early-stage OSCC treated surgically from 2009 to 2014 at our institution were reviewed retrospectively. Histopathological measurement of DOI and TT was performed. The validation of DOI and TT as prognostic factors was conducted using a Kaplan–Meier survival analysis. TT had no association with disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Studies have found DOI, but not TT to be an independent factor in predicting LN metastasis[ 8 , 9 , 14 , 20 ] and significantly associated with locoregional recurrence,[ 13 ] DSS[ 13 , 23 ] and progression-free survival. [ 23 ] A recent meta-analysis found higher DOI to have greater chance of LN metastasis, recurrence and lower survival, corroborating its incorporation for OSCC staging. [ 24 ] Others have found both TT and DOI to carry comparable prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found DOI, but not TT to be an independent factor in predicting LN metastasis[ 8 , 9 , 14 , 20 ] and significantly associated with locoregional recurrence,[ 13 ] DSS[ 13 , 23 ] and progression-free survival. [ 23 ] A recent meta-analysis found higher DOI to have greater chance of LN metastasis, recurrence and lower survival, corroborating its incorporation for OSCC staging. [ 24 ] Others have found both TT and DOI to carry comparable prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors in developed countries use whole slide imaging and carry out precise pDOI measurements. [ 23 ] AJCC recommends ocular micrometry but few authors have questioned its availability in resource-limited setting like India. [ 6 ] Ocular micrometry requires multiple movements of stage to capture entire depth at times or the use of 2× scanner objective and eyepiece.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New effective examination and imaging techniques are being developed that allow the surgeon to better visualize the boundaries of the primary tumor before and during the surgery more precisely [12][13][14][15][16][17][18][19][20][21][22][23][24]. With the help of these techniques, it is possible, among other things, to have a positive impact on margin surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that circular RNA (circRNA) is a kind of non-coding RNA, which has high stability due to its closed circular molecule ( Zheng et al, 2019 ). Studies have shown that circRNA can inhibit its expression by acting as a sponge molecule of microRNA (miRNA), thus regulating the biological processes of tumor cell proliferation, apoptosis, migration, and so on ( Lee et al, 2021 ). However, there are relatively few studies on circRNAs in oral squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%